CIRA: a synopsis of activity, January 1 - December 31, 1983 - Cooperative Institute for Research in the Atmosphere (Fort Collins, Colo.), publisher (Colorado State University. Libraries, 1984)
This third "mid-year" report from the Cooperative Institute for in the Atmosphere (CIRA) is intended to communicate scientific results and information about current activities to NOAA and CSU scientists, students and staff as well as other interested parties.
March 1984.
Keywords: Cooperative Institute for Research in the Atmosphere (Fort Collins, Colo.); Atmosphere -- Research; Meteorology -- Research